Low-study aspects of teaching the Сhinese language as a foreign at the university - Luo Xuan,; Ma Long, (Journal of the Belarusian State University. Philology, 2022)
This article describes the challenges of teaching Chinese as a foreign language to students. The research material was scientific work and teaching aids of Russian, Belarusian and Chinese linguists, methodologists, teachers of Chinese as a foreign language. The analysis of the studied material showed that the poorly studied aspects of foreign language teaching include: ways and methods of recreating the natural language environment, without which high motivation of students is impossible; insufficient use of the contrast-comparative method in the classroom to overcome interlingual interference and the formation of intercultural communicative competence; the issues of cultural connotation of Chinese vocabulary and methods of working on grammatical, lexical and speech errors remain without due attention. As ways of solving problematic issues, the authors propose to conduct joint classes of Belarusian students studying the Chinese language and Chinese students mastering the Russian language on the basis of universities in order to immerse themselves in the cultural and linguistic environment; actively use the Chinese messenger WeChat as a communication educational platform; apply innovative technologies in teaching; develop complexes of online lessons together with Chinese teachers, as well as contribute to the methodology for correcting mistakes in the speech and writing of students; look for ways to overcome the cultural stereotypes of students so that they abandon cultural discrimination; pay more attention to intercultural and linguistic conflict situations so that students can become full participants in intercultural communication.
Keywords: Chinese as a foreign language; teaching foreign languages; communicative method; language environment; linguistic picture of the world; contrast-comparative analysis; speech situations and exercises; cultural connotation; intercultural communicative competence; Republic of Belarus